PROSPECTS FOR THE DEVELOPMENT OF THE "SAFED BULON OR SHOX JARIR" VISIT - TOURIST ROUTE - Abdulxakimov Zuhrali Tursunalievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This state provides information about palomnic tourism, the development of tourism and the development of new directions in the time of the coronavirus pandemic, the history of palomniches in the Namangan region and the Fergana valley, in particular in the Kyrgyz Republic.